FAKTOR PENGARUH SISWA DALAM MEMILIH PERGURUAN TINGGI SWASTA DI KOTA MEDAN - Adri Arianty; Muhammad Fauzan Azhmy; Fajar Pasaribu (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
This study aims to determine what factors can influence students' decisions in choosing a private campus. This type of research is a descriptive quantitative research using primary data, namely questionnaires using Google forms and secondary data in the form of supporting documents. The population in this study was all vocational and high school students in the city of Medan, due to limited time and ability, this study took samples using the Slovin formula so that only 100 respondents were taken as samples. The data analysis model used multiple linear regression tests, classical assumption tests, and hypothesis testing. The results of this study are partially on the transactional factors only promotion factors, Person and physical evidence that have a significant effect on students' decisions to choose a private campus while the influential but not significant factors based on the results of the study are product, price, and location factors. , process. Then the relational factors that have a significant influence are familiarity and professional awareness, while the trust factor has an effect but is not significant. Simultaneously, the factors that exist in transactional (product, price, promotion, person), physical evidence and process) and relational (trust, familiarity, and professional awareness) influence the student's decision to choose a private campus.